Biosorption of Arsenic by Mosambi (Citrus limetta) Peel: Equilibrium, Kinetics, Thermodynamics and Desorption Study - Kamsonlian, Suantak; Suresh, S.; Majumder, C.B.; Chand, S. (Asian Journal of Chemistry, 2012)
The removal of arsenic ions from aqueous solution onto the surface of mosambi peel as biosorbent. Fourier transformation infrared (FTIR), thermogravimetric (TGA) analysis and scanning electron microscopy (SEM) were used to characterize the surface of biosorbent. The effect of process parameters such as pH, temperature, biosorbent dosage and contact time on the performance of biosorption was studied. The biosorbent used in this study was suitable for the removal of arsenic ions with maximum uptake capacity of 2.12 mg g-1 for As(III) and 3.32 mg g-1 for As(V) were obtained at 313 K. Lower percentage removals of arsenic ions were observed with higher initial concentrations. At optimum conditions, the removal of As(III) and As(V) ions were 84.9 % at pH 6 and 89.1 % at pH 4, respectively. Equilibrium sorption data were found to be well fitted to Freundlich isotherm model. Dynamics studies established that the biosorption processes followed pseudo-second order rate equation. The thermodynamic properties of biosorption process were also determined. The values of these properties (-DGº, +DSº and +DHº) indicated that the biosorption process was spontaneous and endothermic in nature.